2021
DOI: 10.1002/mar.21497
|View full text |Cite
|
Sign up to set email alerts
|

How smart experiences build service loyalty: The importance of consumer love for smart voice assistants

Abstract: Smart voice assistants (SVAs) have emerged as new artificial intelligence service platforms. They have the capacity to act like actual human assistants and modify traditional forms of human–computer interactions. So, consumers relate to their SVA as though it was a person, despite knowing that they are interacting with a machine. Based on the stimulus‐organism‐response framework, this paper examines feelings of love that consumers develop for SVAs when they are interacting. It proposes that these feelings act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 131 publications
(176 reference statements)
1
76
0
1
Order By: Relevance
“…We propose a mechanism wherein VA features are signals of either perceptions of VA artificiality or VA intelligence, in turn, these perceptions of artificiality and intelligence affect VA evaluations. In so doing, we assert that VA intelligence provides a more overarching construct than ease of use or usefulness (Table 1; Moriuchi, 2019), and VA artificiality (or its lack) is a more comprehensive construct than feelings of love (Table 1; Hernandez-Ortega & Ferreira, 2021). Formally, we test whether perceptions of reduced artificiality and increased intelligence enhance VA evaluations.…”
Section: Tablementioning
confidence: 94%
“…We propose a mechanism wherein VA features are signals of either perceptions of VA artificiality or VA intelligence, in turn, these perceptions of artificiality and intelligence affect VA evaluations. In so doing, we assert that VA intelligence provides a more overarching construct than ease of use or usefulness (Table 1; Moriuchi, 2019), and VA artificiality (or its lack) is a more comprehensive construct than feelings of love (Table 1; Hernandez-Ortega & Ferreira, 2021). Formally, we test whether perceptions of reduced artificiality and increased intelligence enhance VA evaluations.…”
Section: Tablementioning
confidence: 94%
“…Consequences are factors that result from the influence of antecedents, mediators, and moderators. Noteworthily, the consequences in conversational commerce manifest through a process involving attitudinal acceptance (Fernandes & Oliveira, 2021); intentions such as behavioral intention (Vimalkumar et al, 2021), continuance intention (Ashfaq et al, 2021), purchase intention (McLean et al, 2021), and word-of-mouth intention (Hernandez-Ortega & Ferreira, 2021); actual use behavior (Moriuchi, 2021); experience (Bawack et al, 2021); satisfaction (Loureiro et al, 2021); and post-usage behavior such as addiction (Ramadan, 2021), continuance (Poushneh, 2021b), and loyalty (Hasan et al, 2021).…”
Section: Towards a Conceptual Framework For Conversational Commerce (...mentioning
confidence: 99%
“…As we summarize in Table 2, from a source effect standpoint, various studies have examined VAs and how they might foster customer engagement or prompt subsequent consumer behaviors (Fernandes and Oliveira, 2021;Hernandez-Ortega and Ferreira, 2021;McLean et al, 2021). If VAs signal intelligence, e.g.…”
Section: Ai-enabled Va Researchmentioning
confidence: 99%
“…If VAs signal intelligence, e.g. provide relevant information in response to a service request, then customers will display an increased commitment to the VA brand (Hernandez-Ortega and Ferreira, 2021). The ability of VAs to convey a social presence also has a positive impact (Paul et al, 2021); prior research has shown, mere social presence, whether real or imagined, can motivate purchases (Argo et al, 2005;Dahl et al, 2001).…”
Section: Ai-enabled Va Researchmentioning
confidence: 99%
See 1 more Smart Citation